2009
DOI: 10.2337/db08-1589
|View full text |Cite
|
Sign up to set email alerts
|

Association of Type 2 Diabetes Candidate Polymorphisms in KCNQ1 With Incretin and Insulin Secretion

Abstract: OBJECTIVEKCNQ1 gene polymorphisms are associated with type 2 diabetes. This linkage appears to be mediated by altered β-cell function. In an attempt to study underlying mechanisms, we examined the effect of four KCNQ1 single nucleotide polymorphisms (SNPs) on insulin secretion upon different stimuli.RESEARCH DESIGN AND METHODSWe genotyped 1,578 nondiabetic subjects at increased risk of type 2 diabetes for rs151290, rs2237892, rs2237895, and rs2237897. All participants underwent an oral glucose tolerance test (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
103
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(119 citation statements)
references
References 27 publications
13
103
1
2
Order By: Relevance
“…Moreover, we did not detect any association between the SNPs and insulin resistance based on HOMA-IR values. Thus, we infer that KCNQ1 variants affect glucose metabolism, possibly through impairment of insulin secretion, in line with results from other studies in different populations [6,7].…”
Section: Gctsupporting
confidence: 92%
“…Moreover, we did not detect any association between the SNPs and insulin resistance based on HOMA-IR values. Thus, we infer that KCNQ1 variants affect glucose metabolism, possibly through impairment of insulin secretion, in line with results from other studies in different populations [6,7].…”
Section: Gctsupporting
confidence: 92%
“…34 A study in German population suggested that altered incretin secretion after food intake might be a potential link between KCNQ1 gene variants and impaired b-cells function. 16 In line with their assumption, the KCNQ1 was then be found by RT-PCR to be the most highly expressed K C channel gene-family member in L-cells. 21 Here by double-immunofluorescence staining, KCNQ1 was found to be expressed in GLP-1-positive L-cells in intestinal crypt but not in intestinal villi.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, the variation in KCNQ1 was found to be associated with insulin secretion during oral glucose tolerance test (OGTT) but not intravenous glucose tolerance tests (IVGTT), implying the involvement of indirect mechanisms. 5,16 The glucose-stimulated incretin glucagon-like peptide 1 (GLP-1) was assumed to be a candidate linker between KCNQ1 and b-cells function, 16 but this hypothesis has not been verified so far. A study in gene-targeted mice demonstrated that the KCNQ1 knockout results in enhanced insulin sensitivity and in turn inhibits insulin release, 17 adding more attractiveness over the mechanism by which KCNQ1 exert its effects on b-cells in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Another SNP rs151290 was associated with 30-min C-peptide levels during OGTT, first-phase insulin secretion, and insulinogenic index after adjustment in the dominant model in the population of mainland China [17]. And rs151290 was associated with glucose-stimulated gastric inhibitory polypeptide and GLP-1 increase after adjustment in the dominant model [14]. The molecular mechanism of KCNQ1 SNPs in the intron affects insulin secretion is unclear [6,8,9], suggesting the important role of KCNQ1 in insulin secretion by pancreatic -cells.…”
Section: Kcnq1mentioning
confidence: 95%
“…For rs2237892, rs2237895 and rs2237897 polymorphisms, homozygous carriers of the diabetes-associated allele had significantly decreased BMI (body mass index) and waist circumferences [13]. In German population, the rs2237892, rs2237895 and rs2237897 were nominally associated with OGTT (oral glucose tolerance test)-derived insulin secretion indexes [14]. It has been reported that SNP rs2237892 affected repaglinide and rosiglitazone therapeutic response.…”
Section: Kcnq1mentioning
confidence: 99%